2018
DOI: 10.3390/sym11010007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cobalt Loading, Particle Size, and Calcination Condition on Co/CNT Catalyst Performance in Fischer–Tropsch Reactions

Abstract: The strong electrostatic adsorption (SEA) method was applied to the synthesis of a cobalt (Co) catalyst on a multi-walled carbon nanotube (CNT) support. In order to uptake more of the cobalt cluster with higher dispersion, the CNT was functionalized via acid and thermal treatment. The Co/CNT catalyst samples were characterized by a range of methods including the Brunauer–Emmet–Teller (BET) surface area analyzer, transmission electron microscopy (TEM), X-ray powder diffraction (XRD) analysis, atomic absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…In addition, a significant amount of Co particles are confined in the inner cavity of the tubes (Figure d), which has already been observed for FTS with Co/CNT catalysts . The 15 %Co/CNF catalyst contains relatively large Co particles, which could be due to both low amount of surface oxygen groups and low specific surface area of this support . Some of these particles are confined in the inner cavity of CNF (Figure f).…”
Section: Resultssupporting
confidence: 57%
“…In addition, a significant amount of Co particles are confined in the inner cavity of the tubes (Figure d), which has already been observed for FTS with Co/CNT catalysts . The 15 %Co/CNF catalyst contains relatively large Co particles, which could be due to both low amount of surface oxygen groups and low specific surface area of this support . Some of these particles are confined in the inner cavity of CNF (Figure f).…”
Section: Resultssupporting
confidence: 57%
“…Some researchers recorded the influence of operating conditions on the product selectivity for cobalt-based catalysts [20,24,25] and revealed that the olefin selectivity of the hydrocarbon product range reduced with rising pressure, which has reported in prior studies [19,21,24]. This study is a continuation of previous research that has been examined and published [26][27][28][29][30]. The current investigation aims to prepare cobalt manganese bimetallic catalysts on CNT substrate employing SEA technique, also to study effects of temperature, syngas space velocity, and catalyst stability through Fischer-Tropsch synthesis by performing Co-Mn/CNT bimetallic catalyst.…”
Section: Introductionsupporting
confidence: 70%
“…Bezemer et al reported a higher FTS activity and a higher cobalt active sites on the CNT surface having less than 10 nm particle size distribution on carbon nano-fiber supports [49,50]. Chen et al reported that particle size is not the only role player in an FTS activity but also confinement of catalytic active sites inside CNT support channels has a significant effect (Figure 8d) [51]. Figure 12 shows a decline in selectivity of CH 4 and an increase in C 5+ in the range of 6-8 nm catalyst particle size.…”
Section: Effect Of Ph and Thermal Pre-treatment On Catalyst Propertiementioning
confidence: 98%